2015
DOI: 10.1039/c4sm02717e
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent coordinating self-assembly

Abstract: Self-assemblies dominated by coordination interaction are hardly responsive to thermal stimuli. We show that in case the coordinating mode changes with temperature, the resultant assemblies also exhibit temperature dependence. The self-assemblies are constructed with perylene tetracarboxylate and metal ions. Compounds containing a perylene skeleton often self-assemble into micro-belts, which is also true for the combination of perylene tetracarboxylate and metal ions. However, a unique pinecone structure was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Supramolecular architectures formed by the self-assembly of block molecules have received great attention because of their potential application as advanced functional materials for the development of well-defined supramolecular nanostructures. Among common block molecules such as surfactants, lipid molecules, coil–coil block molecules, supra-amphiphiles, and hybrid complexes, rod–coil molecules with conjugated rod building blocks have proved to be promising scaffolds for the fabrication of various supramolecular nanostructures in response to temperature variations. For example, Lee et al and other research groups systematically investigated linear and variously shaped conjugated rod–coil molecules, including Y-shaped, T-shaped, bent-shaped, propeller-shaped, dumbbell-shaped, and cyclic rod–coil molecules. These molecules spontaneously create well-defined supramolecular assemblies, including 1-D lamellar, 2-D columnar, 3-D hexagonal, and tetragonal structures in either the crystalline or the liquid crystalline phase, depending on molecular shapes and temperatures. Amphiphilic rod–coil molecules consisting of rigid rod segments and flexible hydrophilic poly­(ethylene oxide) (PEO) coil chains are also known to form various supramolecular aggregates with well-defined shapes and sizes, such as spherical micelles, cylindrical micelles, ribbons, vesicles, tubules, helices, and toroids in selected solutions. These self-assembling nanostructures, constructed through noncovalent forces, including hydrophobic and hydrophilic effects, electrostatic interactions, hydrogen bonding, and van der Waals interactions, could be widely utilized as biomimetic or bioinspired materials in aqueous solutions. We reported that supramolecular nanostructures can be accurately controlled by incorporating lateral alkyl groups at the surface of the rod and coil segments or at the center of the rod building block.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular architectures formed by the self-assembly of block molecules have received great attention because of their potential application as advanced functional materials for the development of well-defined supramolecular nanostructures. Among common block molecules such as surfactants, lipid molecules, coil–coil block molecules, supra-amphiphiles, and hybrid complexes, rod–coil molecules with conjugated rod building blocks have proved to be promising scaffolds for the fabrication of various supramolecular nanostructures in response to temperature variations. For example, Lee et al and other research groups systematically investigated linear and variously shaped conjugated rod–coil molecules, including Y-shaped, T-shaped, bent-shaped, propeller-shaped, dumbbell-shaped, and cyclic rod–coil molecules. These molecules spontaneously create well-defined supramolecular assemblies, including 1-D lamellar, 2-D columnar, 3-D hexagonal, and tetragonal structures in either the crystalline or the liquid crystalline phase, depending on molecular shapes and temperatures. Amphiphilic rod–coil molecules consisting of rigid rod segments and flexible hydrophilic poly­(ethylene oxide) (PEO) coil chains are also known to form various supramolecular aggregates with well-defined shapes and sizes, such as spherical micelles, cylindrical micelles, ribbons, vesicles, tubules, helices, and toroids in selected solutions. These self-assembling nanostructures, constructed through noncovalent forces, including hydrophobic and hydrophilic effects, electrostatic interactions, hydrogen bonding, and van der Waals interactions, could be widely utilized as biomimetic or bioinspired materials in aqueous solutions. We reported that supramolecular nanostructures can be accurately controlled by incorporating lateral alkyl groups at the surface of the rod and coil segments or at the center of the rod building block.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the gels remain stable as the temperature amounts to 55 °C (Figure S7), presumably due to the strong coordination interaction that extensively exists within and between the fibers, which are very stable upon increasing temperature. Different from van der Waals attractions that cross-links other physical hydrogels, the coordination interaction can be strengthened at elevated temperature, 63,64 validating the strategy that coordinationtriggered hydrogels are very advantageous in constructing printable biomaterials.…”
Section: Resultsmentioning
confidence: 99%
“…Among various stimuli responsive triggers (heat, light, magnetic field, pH, metal ion, etc. ), light has attracted considerable attention because it works rapidly, reversibly, and remotely, without generating any undesired substances.…”
Section: Introductionmentioning
confidence: 99%